Experiences of informal caregivers after cardiac surgery: a systematic integrated review of qualitative and quantitative studies. Issue 11 (11th November 2019) - Bjørnnes, Ann Kristin; Moons, Philip; Parry, Monica; Halvorsen, Sigrun; Tønnessen, Theis; Lie, Irene
Abstract : Objectives: To provide a comprehensive synthesis of informal caregivers' experiences of caring for a significant other following discharge from cardiac surgery. Design: Systematic integrated review without meta-analysis. Data sources: A bibliographic search for publications indexed in six databases (Cochrane Library, CINAHL, MEDLINE, EMBASE, AMED and PsycINFO), including a scan of grey literature sources (GreyNet International, Google Scholar, Web of Science, WorldCat and the Clinical Trials Registry) was conducted in October 2018. Eligibility criteria for selecting studies: Studies were included if they described views and perspectives of informal caregivers of cardiac surgery patients (non-intervention studies (qualitative and quantitative)), and the effectiveness of interventions to evaluate support programme for informal caregivers of cardiac surgery patients (intervention studies). Results: Of the 4912 articles identified in searches, 42 primary research studies were included in a narrative synthesis with 5292 participants, including 3231 (62%) caregivers of whom 2557 (79%) were women. The median sample size across studies was 96 (range 6–734). Three major themes emerged from the qualitative study data: (1) caregiver information needs; (2) caregiver work challenges and (3) caregivers adaption to recovery. Across the observational studies (n=22), similar themes were found. The trend across seven intervention studies focused on caregiver information needs related to patient disease management and symptom monitoring, and support for caregivers to reduce symptoms of emotional distress. Conclusion: Informal caregivers want to assist in the care of their significant others after hospital discharge postcardiac surgery. However, caregivers feel insecure and overwhelmed and they lack clear/concise discharge information and follow-up support during the early at-home recovery period. The burden of caregiving has been recognised and reported since the early 1990s, but there remains a limited number of studies that assesses the effectiveness of caregiver interventions. PROSPERO registration number: CRD42018096590.